2023
DOI: 10.1001/jama.2023.4034
|View full text |Cite
|
Sign up to set email alerts
|

Added Therapeutic Benefit of Top-Selling Brand-name Drugs in Medicare

Abstract: ImportanceThe Inflation Reduction Act of 2022 authorizes Medicare to negotiate prices of top-selling drugs based on several factors, including therapeutic benefit compared with existing treatment options.ObjectiveTo determine the added therapeutic benefit of the 50 top-selling brand-name drugs in Medicare in 2020, as assessed by health technology assessment (HTA) organizations in Canada, France, and Germany.Design, Setting, and ParticipantsIn this cross-sectional study, publicly available therapeutic benefit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In Reply In our recent article, we found that a majority of Medicare’s top-selling drugs received low added therapeutic benefit ratings by health technology assessment (HTA) organizations in France, Germany, and Canada. Dr Daifotis contends that these assessments are irrelevant to Medicare beneficiaries because they may be based on different “societal judgments and budgetary needs.” This misconstrues an essential part of our analysis: we relied on therapeutic benefit ratings based only on clinical and comparative effectiveness data drawn from the medical literature among other sources, independent of price or budgetary constraints.…”
mentioning
confidence: 98%
“…In Reply In our recent article, we found that a majority of Medicare’s top-selling drugs received low added therapeutic benefit ratings by health technology assessment (HTA) organizations in France, Germany, and Canada. Dr Daifotis contends that these assessments are irrelevant to Medicare beneficiaries because they may be based on different “societal judgments and budgetary needs.” This misconstrues an essential part of our analysis: we relied on therapeutic benefit ratings based only on clinical and comparative effectiveness data drawn from the medical literature among other sources, independent of price or budgetary constraints.…”
mentioning
confidence: 98%
“…This poor return on our health care investment is related to too much (inappropriate) care and very high prices unrelated to therapeutic benefit. For example, the majority of the top-selling pharmaceuticals in Medicare ($19.3 billion) have a low therapeutic benefit compared with alternatives …”
mentioning
confidence: 99%
“…To the Editor A recent article entitled “Added Therapeutic Benefit of Top-Selling Brand-name Drugs in Medicare” relied on a flawed analysis that imported categorical value judgments from other countries to bolster government price-setting policies included in the Inflation Reduction Act.…”
mentioning
confidence: 99%
“…The study authors presented no medical evidence for their conclusions that many treatments “provided low added benefits” to Medicare beneficiaries. The cited foreign health care administrators’ evaluations were also frequently inconsistent, as noted in the article’s supplemental eTable …”
mentioning
confidence: 99%